EFEKTIVITAS KOMUNIKASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI PROGRAM BATARI DI KOTA TARAKAN - Al Mujaddidah Hidayah Amsi; Muhammad Fauzan Ridwan; Zulkarnain Zulkarnain (Pelantar Press, 2025)
This study aims to analyze the effectiveness of Corporate Social Responsibility (CSR) communication in empowering women economically through the Pertamina Berdikari – BATARI Program implemented by PT Pertamina Patra Niaga Fuel Terminal (FT) Tarakan. The BATARI program focuses on improving women's economic independence through training in boneless milkfish processing, strengthening entrepreneurial capacity, and providing digital marketing assistance to the Berkah Joint Business Group (KUB) in Lingkas Ujung Village, Tarakan City. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results show that CSR communication plays an important role in increasing women's capacity and participation, especially through participatory counseling methods, interactive training, and two-way communication between facilitators and participants. The effectiveness of communication is demonstrated by the increased production capabilities, business management skills, and self-confidence of women in independently carrying out economic activities. However, the study also identified challenges such as limited access to technology and digital marketing. Overall, the BATARI program reflects effective and sustainable development communication practices in strengthening the role of women as local economic actors